Re-membering a Queer Body - Holmes, Morgan (UnderCurrents: Journal of Critical Environmental Studies, 1994)
In the spring 1993 issue of The Sciences, Brown University geneticist Anne Fausto-Sterling, citing the work of John Money, indicates that approximately four percent of the population is, to some degree, intersexual: they either possess physical characteristics of both officially recognized sexes or they have chromosomes which indicate a sex which are 'contradicted' by their physical appearance.1 In Toronto, the four percent figure translates into roughly 88,000 people. Yet little has been written about intersexuality, although its concerns often intersect with those of feminist and queer theory. This paper deals with feminist issues in patriarchal medicine and its relation(s) to intersexuality (and intersexuality's inherent ability to challenge arguments for the 'natural' basis of heterosexuality).
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme matérialiste; intersexuation; ontario; personnes intersexes; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2014; sociologie; thématiques; toronto; violences médicales

Les femmes salariées dans l'Église catholique francophone du Québec : une analyse du rôle de l'idéologie et de ses mécanismes dans le maintien des rapports de pouvoir - Bazinet, Colette (Université du Québec à Montréal, 1994)
Keywords: IREF; amériques; discipline; mémoires/thèses; québec; régions géographiques; sciences humaines; sociologie; thématiques; travail

Feminities, masculinities, sexualities: Freud and beyond - Chodorow, Nancy J. (The University Press of Kentucky, 1994)
La psychanalyse peut-elle aller au-delà d'une vision monolithique du genre et de la sexualité normale pour aborder les questions de diversité et de variabilité dans le développement du genre et l'identité de genre ? Ses praticiens et théoriciens peuvent-ils rendre des comptes rendus non pathologisants de la variation de l'orientation sexuelle ? S'appuyant sur une lecture attentive des textes psychanalytiques commençant par Freud et sur sa propre expérience clinique, Chodorow [soutient] que la psychanalyse doit encore démêler la domination masculine de l'hétérosexualité. Elle démontre également le manque de compréhension psychanalytique de l'hétérosexualité et la polarisation problématique des sexualités normales et anormales. Chodorow soutient que la psychanalyse doit prêter attention à la spécificité individuelle et au cadre personnel, culturel et social
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; domination masculine; fem1000; genre; hétérosexisme; hétérosexualité; identités LGBTQIA2+; premier cycle; psychanalyse; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; états-unis

Le pouvoir dans les groupes de femmes de la région de Québec - Couillard, Marie-Andrée (Recherches sociographiques, 1994)
Les idéaux féministes d'égalité formulés au cours des années 1970 et 1980 sont aujourd'hui confrontés à des discours divers qui pénètrent les groupes de femmes. D'une part, la vision des technocrates les incite à accepter des fonctions instrumentales en retour d'un financement considéré essentiel par plusieurs. La majorité des groupes en sont ainsi venus à offrir des services qui se situent dans le prolongement de ceux offerts par le réseau de la santé et des services sociaux. À travers ces ajustements, les groupes de femmes ne se définissent plus seulement comme des lieux de conscientisation et de résistance, mais bien comme des groupes communautaires travaillant, de concert avec d'autres groupes communautaires, à l'amélioration du bien-être collectif. Les discours savants portant sur le féminisme, sur les conditions de sa mise en oeuvre ou sur le rapport entre l'État et le communautaire rejoignent eux aussi les militantes et affectent de façons diverses le portrait qu'elles tracent de leurs pratiques. C'est cet ensemble complexe dans lequel des rapports de force se nouent quotidiennement que nous voulons décrire et analyser ici.
http://id.erudit.org/iderudit/056826ar
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; canada; discipline; groupes de femmes; histoire et politique; militance; patriarcat; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail

Ces femmes qui ont bâti Montréal : la petite et grande histoire des femmes qui ont marqué la vie de Montréal depuis 350 ans - Darsigny, Maryse; Descarries, Francine; Kurtzman, Lyne; Tardy, Évelyne (Les éditions du remue-ménage, 1994)
Plus de 350 chroniques et illustrations, couvrant l’histoire de Montréal depuis sa fondation, répertoriant des réalisations dans tous les secteurs d’activités, des synthèses et des repères chronologiques précieux sous la plume alerte de plus de 150 collaboratrices: journalistes, historiennes, militantes féministes, chercheures, étudiantes, écrivaines…
https://sac.uqam.ca/component/content/article/19-projets-et-publications/publications/femmes/144-ces-femmes-qui-ont-bati-montreal-la-petite-et-la-grande-histoire-des-femmes-qui-ont-marque-la-vie-de-montreal-depuis-350-ans.html
Keywords: SAC; amériques; discipline; histoire; histoire des femmes*; histoire et politique; montréal; politique; québec; régions géographiques; sciences humaines; thématiques

Interventions féministes : parcours et perspectives - De Koninck, Maria; Pâquet-Deehy, Ann; Dennie, Maureen; Savard, Sylvie; Turgeon, Joane (Nouvelles pratiques sociales, 1994)
L'article présente une synthèse des résultats de deux recherches réalisées en concertation et portant sur l'intervention féministe dans les domaines de la santé et des services sociaux au Québec. Recensions d'écrits complétées par une collecte de données auprès d'intervenantes oeuvrant sur le terrain, les recherches ont permis de constater que l'intervention féministe se répand et se diversifie. À partir de ce constat, les auteures proposent des réflexions et soulèvent des questions sur la pertinence, les possibilités et les mécanismes pouvant favoriser la recherche théorique sur la base des pratiques.
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; cours; discipline; intervention sociale; périodes historiques; québec; régions géographiques; santé; santé des femmes*; sciences humaines; thématiques; travail social; trs3500

Feminism and postmodernism - Ferguson, Margaret; Wicke, Jennifer (Duke University Press, 1994)
This collection of essays explores the significant agreements and tensions between contemporary feminist and postmodern theories and practices. Having brought enormous changes to conceptions of the body, identity, and the media, postmodernity compels the rethinking of many feminist categories, including female experience, the self, and the notion that "the personal is political." Feminist analysis has been equally important, though not always equally acknowledged, as a force within postmodernism. Feminist writings on subjectivity, master narratives, and the socioeconomic underpinnings of the master narrative of theory itself have been particularly influential. This volume traces the crossings and mutual interrogations of these two traditions into the arenas of cultural production, legal discourse, and philosophical thought. Multidisciplinary and international in their collective focus, the essays range from a study of Madonna as an Italian American woman who is revising the cultural meanings of an ethnic feminism to a unique interview with Mairead Keane, the national head of the Women’s Department of the Irish political party Sinn Fein. Turning the prism of postmodern feminism onto such diverse cultural objects as literary and literary critical texts, contemporary film, and music, these essays intervene in debates regarding technology, sexuality, and politics. Challenging modern feminisms to articulate their inescapable relation to postmodern society, this expanded edition of a special issue of boundary 2 also explores ways in which feminism can work as the cutting edge of a global postmodernism. Contributors. Salwa Bakr, Claire Detels, Margaret Ferguson, Carla Freccero, Marjorie Garber, Barbara Harlow, Laura E. Lyons, Anne McClintock, Toril Moi, Linda Nicholson, Mary Poovey, Andrew Ross, David Simpson, Kathyrn Bond Stockton, Jennifer Wicke
Keywords: amériques; approches et analyses; cours; discipline; fem1000; féminisme pop; irlande; philosophie; postmodernisme; premier cycle; régions géographiques; sciences humaines; troisième vague; états-unis; études culturelles

The Women’s Art Society of Montreal: A Century of Commitment to the Arts - Holowach-Amiot, Elaine (Musée McCord d'histoire canadienne, 1994)
The Women's Arts Society of Montreal was founded in 1894 by Mary Martha Phillips and Mrs. James H. Peck (nee Mary Alice Skelton). The parent body of the Society (The Women's Art Association of Canada) was incorporated in Toronto in 1892. The goal of the Montreal Society was to integrate women into the art world at a time in history when women had few rights and were relegated to other roles. In 1907, the Montreal branch of the Women's Art Association of Canada broke away from the Toronto organization to form their own independent society. During and after the First World War, the Women's Arts Society of Montreal focussed on philanthropic efforts, assisting disabled and convalescing veterans and their families. After 1938, the Society’s efforts shifted towards entertainment and other branches of the arts, such as theatre, music and studio art. In the late 1990s the Society began to accept men as members.
Keywords: 1800-1899; 1900-1999; amériques; discipline; groupes de femmes; histoire; histoire des femmes*; montréal; périodes historiques; régions géographiques; sciences humaines; sofia; thématiques; travail

Paradoxes of gender - Lorber, Judith (Yale University Press., 1994)
In this innovative book, a well-known feminist and sociologist challenges our most basic assumptions about gender. Judith Lorber argues that gender is wholly a product of socialization, subject to human agency, organization, and interpretation, and that it is a social institution comparable to the economy, the family, and necessity of gender, she envisions a society structured for equality, where no gender, racial, ethnic, or social class group is allowed to monopolize positions of power.
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; fem1000; genre; identités LGBTQIA2+; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; socialisation; sociologie; thématiques; états-unis

Sexes et pouvoir : la construction sociale des corps et des émotions - Préjean, Marc (Presses de l'Université de Montréal, 1994)
Keywords: 1900-1999; 1990-1999; amériques; care; corps; cours; différence des sexes; discipline; fem1000; militance; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sociologie; thématiques; émotions